The Effectiveness of an Integrated Educational Package of Growth Mindset and Time Perspective on Personal Growth Initiative and Social–Emotional Competence of Students - Azadikhah, Zeinab; Dadvand, Fatemeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective:  The present study aimed to examine the effectiveness of an integrated educational package based on growth mindset and time perspective on personal growth initiative and social–emotional competence among upper secondary school students.Methods and Materials: This study was conducted using a randomized controlled trial with a pretest–posttest–follow-up design and a control group. The participants consisted of 30 upper secondary school students from Shiraz, Iran, who were randomly assigned to an experimental group (n = 15) and a control group (n = 15). The experimental group received an integrated educational intervention combining growth mindset and time perspective principles over structured group sessions, while the control group received no intervention during the study period. Data were collected at three time points: pretest, posttest, and a five-month follow-up. Personal Growth Initiative and Social–Emotional Competence were assessed using standardized self-report questionnaires. Data analysis was performed using repeated-measures analysis of variance in SPSS version 27.Findings: The results of repeated-measures ANOVA indicated significant main effects of time and group, as well as significant time × group interaction effects for both personal growth initiative and social–emotional competence (p < .001). Bonferroni post-hoc comparisons showed that the experimental group demonstrated significant improvements from pretest to posttest in both variables, and these gains were largely maintained at the five-month follow-up, whereas no significant changes were observed in the control group.Conclusion: The findings suggest that an integrated educational package combining growth mindset and time perspective is effective in enhancing personal growth initiative and social–emotional competence among upper secondary school students, with effects that remain relatively stable over time.